2021
DOI: 10.1029/2021jb021846
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and Upper Mantle Structure Beneath the Southeastern United States From Joint Inversion of Receiver Functions and Rayleigh Wave Dispersion

Abstract: Using data from 186 stations belonging to the USArray Transportable Array, a three‐dimensional shear wave velocity model for the southeastern United States is constructed for the top 180 km by a joint inversion of receiver functions and Rayleigh wave phase velocity dispersion computed from ambient noise and teleseismic earthquake data. The resulting shear wave velocity model and the crustal thickness and Vp/Vs (κ) measurements show a clear spatial correspondence with major surficial geological features. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…This leads to densification and delamination of the crust's bottom (Bousquet et al., 1997; Rey, 1993). Such crustal thinning by delamination has been suggested in other regions along the southeastern passive continental margin, including the Carolina Terrane and Inner Piedmont of the southern Appalachian Mountains (Parker et al., 2013; Q. Yang et al., 2021).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This leads to densification and delamination of the crust's bottom (Bousquet et al., 1997; Rey, 1993). Such crustal thinning by delamination has been suggested in other regions along the southeastern passive continental margin, including the Carolina Terrane and Inner Piedmont of the southern Appalachian Mountains (Parker et al., 2013; Q. Yang et al., 2021).…”
Section: Discussionmentioning
confidence: 73%
“…The procedures and parameters for the determination of the prior and posterior distributions closely followed the method of Shen et al. (2013), with applications for regional investigations in the continents of North America and Africa (Shen & Ritzwoller, 2016; T. Wang et al., 2022; Q. Yang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the observed crustal anisotropy also disfavors the presence of an organized lower crust flow in the eLVZ area. In fact, all the most recent tomographic studies (e.g., Y. Yang et al., 2020; X. Yang et al., 2023; Zhang et al., 2020) showed that the eLVZ is disconnected from the wLVZ, suggesting that it has a different origin from the wLVZ, such as mantle upwelling (Z. Huang et al., 2015) or crustal thickening and partial melting in the mid‐lower crust (Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As river incision data supported the lower crust flow model for the crustal uplift in this area (Clark et al., 2005), many magnetotelluric and seismic investigations have been conducted to image the lower crustal flow. While magnetotelluric images suggested that high electrical conductivity structures in the lower crust are localized in two continuous channels that run roughly from north to south (Bai et al., 2010), seismic images, on the other hand, showed two distinct LVZs beneath the SYRB and the SCB (e.g., Bao et al., 2015; M. Chen et al., 2014; Y. Liu et al., 2023; Shen et al., 2016; Y. Yang et al., 2020; X. Yang et al., 2023; Zhang et al., 2020). The two LVZs seem to be separated by the inner zone of the ELIP and will be referred to as eLVZ and wLVZ, respectively (Figure 7b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation